Managing patients with advanced soft tissue sarcoma: Evolving landscape from an Australian perspective. Issue 6 (30th January 2022) - Bae, Susie; Brnabic, Alan; Crowe, Philip; Carey‐Smith, Richard; Andelkovic, Vladimir; Singhal, Nimit; Stalley, Paul; Yip, Desmond; Desai, Jayesh
Abstract: Aim: Despite lack of advances in the first‐line systemic therapy, the overall survival (OS) has continued to improve in patients with advanced soft tissue sarcoma (STS) with the recent estimation of median OS at 20 months. Several systemic therapy options are available now for the second‐line and beyond, with more treatment tailored to histology and molecular subtype. The aim of this retrospective study was to characterize current patterns of care in managing patients with advanced STS (aSTS) in Australia. Methods: Sarcoma databases from 7 Australian sarcoma services were accessed to identify patients diagnosed with locally advanced inoperable and/or metastatic STS between January 1, 2010 and December 31, 2015. Baseline clinicopathological factors and initial treatment patterns were descriptively analyzed. For the Victorian cohort where treatment of aSTS and follow‐up details were available, further exploratory analysis was conducted to determine the impact of patient and tumor characteristics and the use of palliative‐intent treatment OS. Results: Of 2261 cases of STS, 671 were deemed as aSTS. Two thirds were relapsed disease with a mean 1.9 years from initial diagnosis. Median age at diagnosis of aSTS was 59 years (18–95 years) and 56.3% was male. Histology classification revealed four main subtypes: undifferentiated pleomorphic sarcoma (UPS) (23.1%), leiomyosarcoma (18.2%), liposarcoma (12.8%), synovial sarcoma (8.2%), and other comprising 14 STS subtypes. For the Victorian cohort ( N = 361), approximately 80% of patients accessed palliative‐intent treatment of various modalities. Nearly 40% of patients underwent tumor‐debulking surgery or metastasectomy, of which lung wedge resection was the most common ( N = 83, 47.7%). A total of 438 palliative‐intent radiotherapy treatments were delivered to 259 patients (71.7%), with the majority in the form of external beam radiotherapy. Palliative‐intent systemic therapy was delivered to 51.5% of patients ( N = 186), mostly (73%). Anthracycline‐based therapy was the most commonly delivered therapy ( N = 135, 72.6%). Approximately half of the patients in each line of therapy failed to proceed to the subsequent line of systemic therapy with 29.4% receiving three or more lines of therapy ( N = 55). A total of 18.3% of patient ( N = 34) participated in clinical trials or accessed off‐label drugs. The median OS for the Victoria cohort was 15.4 months (95% confidence interval: 12.1, 18.2). The UPS histology subtype was associated with poorer OS, whereas receiving any modality of palliative‐intent treatment conferred survival benefit. Conclusion: In Australia, aSTS is managed with diverse treatment approaches comprising various therapy modalities. Further work is planned in describing healthcare resource utilization and estimating costs by this patient cohort. Abstract : A retrospective cohort study was conducted to characterize treatment patterns in managing advanced soft tissue sarcoma at Australian sarcoma referral centers. Our findings highlight the highly variable course of patient journey in this incurable setting with the use of systemic therapy and frequent use of local therapies.